solve and explain step by step.
Attachments:
![](https://hi-static.z-dn.net/files/d51/de550ad86b87710b090cfa258a165427.jpg)
Answers
Answered by
0
Step-by-step explanation:
this is the answer of your question
Attachments:
![](https://hi-static.z-dn.net/files/de2/c63ef47a0ed082bbe72d036100b7c024.jpg)
Answered by
0
Answer:
X+1=0
X= -1
-1 is the zero.
Step-by-step explanation:
=>2x⁴+ 7x³+4x²-7x-9
=>2×(-1)⁴+7×(-1)³+4×(-1)²-7×(-1)-9.
We have replaced x to -1 as it is the zero of the factor.
=>2×1 + 7×-1+4×1+7-9
=> 2-7+4-2
=>-7+4
=>-3
Here is your answer I guess.
Similar questions